A Trigger for Opioid Misuse: Chronic Pain and Stress Dysregulate the Mesolimbic Pathway and Kappa Opioid System - Massaly, Nicolas; Morón, Jose A.; Al-Hasani, Ream (Frontiers in Neuroscience, 2016)
Pain and stress are protective mechanisms essential in avoiding harmful or threatening stimuli and ensuring survival. Despite these beneficial roles, chronic exposure to either pain or stress can lead to maladaptive hormonal and neuronal modulations that can result in chronic pain and a wide spectrum of stress-related disorders including anxiety and depression. By inducing allostatic changes in the mesolimbic dopaminergic pathway, both chronic pain and stress disorders affect the rewarding values of both natural reinforcers, such as food or social interaction, and drugs of abuse. Despite opioids representing the best therapeutic strategy in acute pain conditions, they are often misused as a result of these allostatic changes induced by chronic pain and stress. The kappa opioid receptor system is critically involved in these neuronal adaptations in part through its control of dopamine release in the nucleus accumbens. Therefore, it is likely that changes in the kappa opioid system following chronic exposure to pain and stress play a key role in increasing the misuse liability observed in pain patients treated with opioids. In this review, we will discuss how chronic pain and stress-induced pathologies can affect mesolimbic dopaminergic transmission, leading to increased abuse liability. We will also assess how the kappa opioid system may underlie these pathological changes.